2021
DOI: 10.3389/fgene.2021.612492
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and Whole-Genome Resequencing of Welsh Sheep Breeds Reveal Candidate Genes and Variants for Adaptation to Local Environment and Socioeconomic Traits

Abstract: BackgroundAdvances in genetic tools applied to livestock breeding has prompted research into the previously neglected breeds adapted to harsh local environments. One such group is the Welsh mountain sheep breeds, which can be farmed at altitudes of 300 m above sea level but are considered to have a low productive value because of their poor wool quality and small carcass size. This is contrary to the lowland breeds which are more suited to wool and meat production qualities, but do not fare well on upland past… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 81 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…Moreover, the NBEA has been found in a selection signature in a worldwide sheep analysis, and it was reported to be under selection in Northern Eurasian human populations adapted to severe climate (Khrunin et al., 2020). Other genes related to the adaptation to the environment are related to vision, RNF24 and the PANK2, that were found to be under selection in Welsh lowland sheep breeds (Sweet‐Jones et al., 2021). These two genes, detected in ROH islands on the OAR13 associated with animals living in hill and plain, were associated with a loss of vision following domestication (Naval‐Sanchez et al., 2018; Wang, Zhang, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the NBEA has been found in a selection signature in a worldwide sheep analysis, and it was reported to be under selection in Northern Eurasian human populations adapted to severe climate (Khrunin et al., 2020). Other genes related to the adaptation to the environment are related to vision, RNF24 and the PANK2, that were found to be under selection in Welsh lowland sheep breeds (Sweet‐Jones et al., 2021). These two genes, detected in ROH islands on the OAR13 associated with animals living in hill and plain, were associated with a loss of vision following domestication (Naval‐Sanchez et al., 2018; Wang, Zhang, et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that Subei yak showed excellent muscle fat deposition and meat quality traits. In addition, among the genes signi cantly enriched in the pathway, the study also found a gene 3-hydroxy-3methylglutaryl-coenzyme A synthase 1 (HMGCS1) associated with lactation persistence[56], melanocortin-1-receptor (MC1R) associated with coat color [57,58], and an essential regulator in the immune system factor regulatory factor X-5 (RFX5) [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…The reads were mapped to the reference genome (ARS-UCD1.2) and the average coverage of these samples is 11.64×. Then, 20,546,726 biallelic SNPs discovered in these 30 Xia'nan cattle were annotated. Functional annotation of SNP sites showed that the majority of SNPs were located in intergenic regions (58.8%) or intronic regions (37.5%).…”
Section: Sequencing Mapping and Snp Detectionmentioning
confidence: 99%